China Business: the relation between media and power in the Geisel Government Diplomacy (1974-1979) - Müller, Pricila Niches (Revista Crítica Histórica, 2020)
This paper deals with relations between the press and foreign policy in Brazil, focusing on the analysis of the position of press agencies regarding the foreign policy of the Geisel government (1974-1979), which sought to diversify partnerships with the employment of a so-called “pragmatic, responsible and ecumenical” policy, with emphasis on the initial establishment of the strategic partnership with the China Popular Republic, including at embassies level between both countries. Thus, the main objective of the study is to investigate how the formation of partnership between Brazil and China is portrayed in the mainstream Brazilian press in the context of the years that comprise the Geisel Government. This article deals specifically with the representation made by the press about Presidential Inauguration. Ernesto Geisel and the government's foreign policy, as well as an analysis of the issue involving the press and “public opinion”. The study was based on specialized literature and documentation analysis of two of the largest print media of the time: The State of São Paulo and Jornal do Brasil. It is important to emphasize that this study is part of a larger work on the subject, developed in my master's dissertation by PUCRS PPGH.